Ethical hacking : understanding how the good guys find system and web app vulnerabilities before the bad guys do - Messier, Ric (O'Reilly, 2017)
"Ethical hacking, or security testing, is the art and science of finding the flaws in an organization's network systems or web applications. Identifying those vulnerabilities can give the organization a fighting chance to fix them before the bad guys find them. This course is a hands-on overview of the open source tools that information security professionals use to conduct professional caliber penetration tests. Prerequisites include a basic understanding of the ways network systems and operating systems work, basic familiarity with Linux, the ability to run virtual machines (VMWare, etc.) so you can set up attack systems and target systems, and a computer that's ready to run Kali Linux and Metasploit software."--Resource description page.